PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI DIMENSI TIGA - Foahonoa Zisokhi Nehe (Universitas Nias Raya, 2024)
This research aims to determine whether there is an influence of the CTL learning model on students' ability to understand mathematical concepts in three-dimensional material. This research approach is a quantitative approach with a quasi-experimental type of research. The population of this study was class XII of SMA Negeri 1 Teluk Dalam in the 2023/2024 academic year, consisting of 262 students. Samples were taken using the Cluster Random Sampling technique, namely class XII Science-Melati (Experiment) 34 students and XII Science-Teratai (Control) 26 students. The instrument used is a test of students' ability to understand mathematical concepts in three-dimensional material. The results of research data processing showed that the average Pretest score for the experimental class was 65.59 and the control class was 65.38 and the Posttest for the experimental class was 72.03 and the control class was 66.12. Hypothesis testing using the Independent-Samples T Test shows that the sig (2-tiled) value is 0.048 < 0.05, meaning there is a significant difference in the posttest scores for the two classes. It was concluded that the CTL learning model influenced students' ability to understand mathematical concepts in three-dimensional material. This is influenced by students who play an active role in discovering concepts of learning material through real experience and collaboration in discussions with friends and teachers. Researchers suggest (1) The CTL learning model is an alternative for teachers to build students' ability to understand mathematical concepts (2) Students are advised to seek and build understanding of learning material through their knowledge of the real world (3) The results of this research should be taken into consideration by researchers Next in choosing a learning model.